2023
DOI: 10.1108/sajm-06-2022-0040
|View full text |Cite
|
Sign up to set email alerts
|

Neobanking adoption – An integrated UTAUT-3, perceived risk and recommendation model

Abstract: PurposeThe authors aim to study a conceptual model based on behavioural theories (UTAUT-3 model) to evaluate the adoption, usage and recommendation for neobanking services in India.Design/methodology/approachThe authors propose this model based on the UTAUT-3 integrated with perceived risk constructs. Hypotheses were developed to determine the relationships and empirically validated using the PLSs-SEM method. Using the survey method, 680 Delhi NCR respondents participated in the survey.FindingsEmpirical result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…To examine the nonresponse bias, one-third of the responses received from early respondents were compared with the last one-third of responses using a t -test of group means (Bhatnagr and Rajesh, 2023; Hwang and Kim, 2018). The findings show no significant effect among the two groups; therefore, nonresponse bias is not considered problematic.…”
Section: Methodsmentioning
confidence: 99%
“…To examine the nonresponse bias, one-third of the responses received from early respondents were compared with the last one-third of responses using a t -test of group means (Bhatnagr and Rajesh, 2023; Hwang and Kim, 2018). The findings show no significant effect among the two groups; therefore, nonresponse bias is not considered problematic.…”
Section: Methodsmentioning
confidence: 99%
“…According to the degree of uncertainty a person has about a given behavior, perceived risk relates to how that person perceives the potential consequences of an action. People seek to avoid risks while making decisions in risky situations as much as possible, which can be done by taking precautions [47,48]. Risks such as security may affect the behavior and intention of an individual to adopt low-code/no-code technology [40].…”
Section: Perceived Risksmentioning
confidence: 99%
“…Figure 2, the conceptual framework utilized in this study is developed based on the UTAUT model, alongside other constructs identified in the literature regarding EV adoption. Aligned with the UTAUT model, key independent variablesperformance expectancy, effort expectancy, social influence and facilitating conditionsare utilized to gauge purchase intention (Bhatnagr and Rajesh, 2023;Venkatesh et al, 2003). Additionally, acknowledging the significance of environmental concerns in influencing consumer behavior toward EV adoption, environmental concern is also integrated as an independent variable (Noel and Sovacool, 2016), complementing the UTAUT model variables.…”
Section: Conceptual Frameworkmentioning
confidence: 99%